Особливості формування молочної продуктивності корів червоної степової породи - Лесновська, Олена Володимирівна; Lesnovska, O. V.; Lesnovskay, O. V.; Lesnovska, E. V.; Lesnovskay, E. V.; Lesnovska, O. W.; Lesnovska, E. W.; Lesnovskay, O. W.; Lesnovska, O. W.; Карлова, Ліна Валентинівна; Karlova, L. V.; Karlova, L.; et al. (Дніпровський ДАЕУ, 2019)
Тривалість та умови розвитку плода, його жива маса при народженні є показниками, що мають не лише загальнобіологічне значення, але й можливі селекційні ознаки. Усе частіше наголошується необхідність добору молодняку з урахуванням тривалості ембріонального розвитку та його вплив на подальшу молочну продуктивність і відтворювальну здатність. Дослідження проводили в ТОВ “Обрій” Покровського району Дніпропетровської області на телицях червоної степової породи (n = 150). Виділено чотири групи телиць: з коротким, середнім, подовженим і оптимальним утробним розвитком. У телиць визначали показники росту та розвитку, продуктивність, відтворювальну здатність. Провели економічний моніторинг доцільності використання телиць досліджуваних групп шляхом підрахунку кількості одержаної додаткової продукції. Встановлено, що в 72,7% телиць тривалість утробного розвитку становила 280–290 діб. Відповідно 19,3 та 8,0% телиць мали короткий і подовжений утробний розвиток. В основні періоди вирощування найбільшу живу масу мали телички з періодом утробного розвитку 290 діб і більше. Однак за середньодобовими приростами живої маси перевага була на боці особин, у яких період утробного розвитку становив 286–290 діб. Так, цей показник у теличок ІІ–ІV групп від народження до 6-місячного віку становив 656,7–684 г, що більше на 3,1–7,5%, ніж у особин із періодом утробного розвитку 279 діб і менше. Аналогічна тенденція спостерігалася в періоди вирощування 6–12 та 12–18 місяців. Порівняно з теличками І групи перевага становила 10,9–13,8% і 2,7–7,0%, відповідно. У 24-місячному віці також кращі прирости мали особини ІІ–ІV груп: 468,9–480,5 г, тоді як у ровесниць І дослідної групи цей показник дорівнював 401,1 г. Дослідженнями виявлено, що жива маса визначає і вік першого осіменіння телиць. Жива маса ремонтних телиць дослідних груп за першого осіменіння коливалася в межах 363,8–398,5 кг в розрізі груп, тобто 75–80% живої маси повновікової корови, що є оптимальним показником для відтворення стада. Так телиці ІІ–ІV дослідних груп були запліднені на 71,0–46,9 доби раніше, тобто у віці 548,3–572,4 доби, порівняно з аналогами І дослідної групи. В особин ІІ–ІV груп перші телята отримані у віці 819,4–840,1 доби. Перевагу за живою масою особини цих дослідних групп утримували і за першого отелення: від 467,2 до 519,6 кг. Зазначимо, що тут і вихід телят на 100 корів більше на 0,4–6,3% порівняно з первістками І групи. Результати досліджень молочної продуктивності показують, що тварини І дослідної групи в першу лактацію на 2,8% відставали від стандарту породи з надоєм 2818,4 кг. У другу та третю лактації відмічено збільшення відставання від стандарту породи на 3,9% та 4,6%. Корови ІІ–ІV дослідних за молочною продуктивністю переважали вимоги стандарту породи. Якісні показники молока в розрізі дослідних груп були неоднакові. Так, уміст жиру і білка в первісток І групи протягом дослідного періоду коливався в межах 3,66–3,71% та 3,30–3,31%, а в однолітків ІІ–ІV дослідних груп ці показники дорівнювали 3,71–3,73% та 3,31–3,33%, відповідно. Таким чином, середня й оптимальна тривалість ембріонального розвитку (280–285 та 286–290 діб) та інтенсивний ріст телиць у постембріональний період позитивно в подальшому впливають на рівень їх продуктивних показників. Середня прибавка до основної продукції корів червоної степової породи ІІ–ІV дослідних груп, порівняно з однолітками І групи, була в межах 8,4–11,9%. Duration and conditions of fetus development, its live weight at birth are indicators that have not only general biological significance, but also possible breeding characters. Even more often, the need for selection of young animals is noted with an allowance for duration of embryonic development and its influence on further milk productivity and reproductive capacity. The research was carried out in LLC “Obriy” of Pokrovskyi district of the Dnipropetrovsk region on heifers of red steppe breed (n = 150). Four groups of heifers are selected: with short, medium, elongated and optimal uterine development. By heifers were determined the growth and development indicators, productivity, reproductive capacity. Economic monitoring had been carried out by us relative to expediency of using the heifers of the under-investigation groups by counting the amount of additional products received. It was established, that in 72.7% of heifers the duration of uterine development was 280–290 days. Accordingly, 19.3% and 8.0% of heifers had short and prolonged uterine development. In the main growing periods, the largest live weight had heifers with the period of uterine development of 290 days or more. However, on average daily gains of live weight, the advantage was on the side of individuals, in which the period of uterine development was 286–290 days. Thus, this indicator in heifers of ІІ–ІV groups from birth to 6 months of age was 656.7–684 g, which is more by 3.1–7.5% than those with the period of uterine development of 279 days or less. A similar trend was observed during growing periods of 6-12 and 12-18 months. Compared to heifers of Group I, the advantage was 10.9–13.8% and 2.7–7.0%, respectively. In the 24-monthold age, the best gains were in individuals of ІІ–ІV groups: 468.9–480.5 g, while in the age group І the experimental group, this indicator was 401.1 g. The research have shown that live weight determines the age of the first insemination of heifers. The live weight of the repair heifers of the experimental groups for the first insemination ranged from 363.8 to 398.5 kg in the group, that is 75–80% of live weight of the full-age cow, which is the best indicator for reproduction of theherd. So the heifers of ІІ–ІV experimental groups were inseminated at 71.0–46.9 days earlier, that is, at the age of 548.3–572.4 days, compared to the analogues of the first experimental group. In the individuals of ІІ–ІV groups, the first calves were obtained at the age of 819.4–840.1 days. The advantage for live weight of the individuals of these experimental groups was retained for the first calving: from 467.2 to 519.6 kg. It should be noted that here and the output of calves for 100 cows is more by 0,4–6,3% compared to the first heifers of the first group. The results of milk productivity studies show that animals of the first experimental group in the first lactation by 2.8% lagged behind the standard breed with milk yield of 2818.4 kg. In the second and third lactation, an increase in the lagging behind the breed standard by 3.9% and 4.6% was noted. Cows of II–IV of the experimental groups on milk productivity exceeded the requirements of the breed standard. Qualitative indicators of milk from the point of view of experimental groups were unequal. Thus, the fat and protein content of the first heifers of Group I during the experimental period fluctuated within the range of 3.66–3.71% and 3.30–3.31%, while in the peers of ІІ–ІV experimental groups, these indicators were 3.71–3.73% and 3.31–3.33%, respectively. Thus, the average and optimal duration of embryonic development (280–285 and 286–290 days) and the intensive growth of heifers in the post-embryonal period positively influence the level of their productive indicators in the future. The average increase to the main products of the cows of the red steppe breed of the II–IV experimental groups, in comparison with the peers of the first group, was within the range of 8.4–11.9%.
Features of Formation of Milk Productivity of Cows of Red Steppe Breed
Лесновська Олена Володимирівна https://orcid.org/0000-0002-9027-6734 Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588
Keywords: репродуктивна здатність; reproductive capacity; ембріогенез; embryogenesis; телиці; heifers; продуктивність; productivity